The expressive and writing workshop as a means to promote self-expression in disability - Vargiu, Yuri (Formazione & insegnamento, 2021)
The activities designed for patients of Disability Day Care Centres are meant to encourage them to experiment with their motor and cognitive functions, and possibly improve them over time. The establishment of Artistic Workshops gives participants a chance to express themselves freely through a wide range of tools, both graphic-visual and narrative-literary. The ultimate goal would be channelling the patients’ creativity and imagination, aided by themes and guidelines suggested by the staff, into the production of works of art, at the same time discovering more about one’s inner self as well as the outside world. Furthermore, based on existing research, encouraging patients to explore and understand the connection between each piece they craft has proven beneficial. This paper will detail the methods used by the staff of a Day Care Centre for Disability in the creation and development of a Workshop in Artistic Expression and Creative Storytelling for patients.